Character Values of Dewi Siti Sarijati's Oral Stories in Sluke Village, Rembang Regency - Mohammad Kanzunnudin; Ahdi Riyono; Noor Rina Kastatria; Arceli R. Millan (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2025)
Sluke Village, Sluke District, Rembang Regency, Central Java, is a coastal area. The characteristics of coastal areas produce a culture in the form of folklore with various forms, such as fairy tales, proverbs, parikan (pantun), and seloka. One of the oral folklore that is very famous and has not been studied by other researchers from the perspective of character values, namely the oral story "Dewi Siti Sarijati". Therefore, it is very appropriate to be studied. The purpose of this study is to analyze the character values contained in the oral story of Dewi Siti Sarijati. This study uses descriptive qualitative methods. The data are in the form of fragments of the story of Dewi Siti Sarijati, and the data sources are the results of interviews with informants (community leaders, practitioners, teachers, writers, and officials, who understand the story of Dewi Siti Sarijati). Data collection techniques include (1) literature study, (2) observation, (3) interviews, (4) recording, (5) note-taking, and (6) transcription. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the oral story of Dewi Siti Sarijati has comprehensive character values in the form of religious values, nationalism, independence, mutual cooperation, and integrity. This proves that the oral story "Dewi Siti Sarijati" from Sluke Village, Sluke District, Rembang Regency, Central Java, can be used as material for character education. Therefore, in general, folklore can be used as a means to strengthen national character.    Desa Sluke, Kecamatan Sluke, Kabupaten Rembang, Jawa Tengah,  merupakan wilayah pesisir. Karakteristik wilayah pesisir menghasilkan kebudayaan berupa cerita rakyat dengan berbagi bentuknya, seperti dongeng, pepatah, parikan (pantun), dan seloka. Salah satu cerita rakyat lisan yang sangat terrkenal dan belum diteliti oleh peneliti lain dari sudut nilai karakter, yakni cerita lisan “Dewi Siti Sarijati”. Oleh sebab itu, sangat tepat untuk diteliti. Tujuan penelitian ini untuk menganalisis nilai karakter yang terdapat dalam cerita lisan Dewi Siti Sarijati. Penelitian ini menggunakan kualitatif deskriptif. Data berupa penggalan cerita Dewi Siti Sarijati dan sumber datanya hasil wawancara pada para narasumber (tokoh masyarakat, praktisi, guru, penulis, pejabat, yang memahami cerita Dewi Siti Sarijati). Teknik pengumpulan data melalui (1) studi pustaka, (2) observasi, (3) wawancara, (4) perekaman, (5) pencatatan, dan (6) transkripsi. Teknik analisis data dengan reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa cerita lisan Dewi Siti Sarijati memiliki nilai karakter secara komprehensi berupa nilai religius, nasionalisme, mandiri, gotong royong, dan integritas. Hal ini membuktikan bahwa cerita lisan “Dewi Siti Sarijati”  di Desa Sluke, Kecamatan Sluke, Kabupaten Rembang, Jawa Tengah; dapat dijadikan materi dalam pendidikan karakter. Oleh sebab itu,  secara umum cerita rakyat dapat dijadikan sarana untuk penguatan karakter bangsa.